Teacher talking time in the efl classroom (2005)
This paper reports on a piece of classroom research, aiming to support the hypothesis that most of the talk in my English-as-a-foreign-language elementary and intermediate classrooms was done by the teacher, presumably implying a more teacher-centred approach. In terms of the percentage of teacher talk, the results indicate that the discrepancy between the amount of teacher talk actually done in these classrooms and that which was hypothesized as being in conflict with a learner-centred approach was notably high. This appears to imply that, although I talked more than the learners on some occasions, my lessons were much more focused on them rather than on me, the teacher. Key words: Classroom research, teacher talking time, learner-centred approach, English as a foreign language, teacher-centred approach Este documento reporta sobre una investigación realizada en el aula, con el fin de comprobar la hipótesis de que el profesor hizo la mayor parte de las intervenciones orales en las clases de inglés como lengua extranjera en los niveles elemental e intermedio, lo que implica presumiblemente un enfoque más centrado en el profesor. En términos del porcentaje de intervención del profesor, los resultados indican que la discrepancia entre el volumen de su participación oral en las aulas y el que según la hipótesis conduciría a un conflicto con el enfoque centrado en el estudiante, fue notablemente alta. Esto parece indicar que, aunque en ocasiones mi participación oral fuera mayor que la de los estudiantes, mis lecciones se centraron mucho más en ellos que en mí, el profesor. Palabras claves: Investigación en el aula, tiempo de participación oral del profesor, enfoque centrado en el estudiante, inglés como lengua extranjera, enfoque centrado en el profesor